پاکستان میں مروج تکافل کی شرعی حیثیت اور فقہی تکییف-ایک تحقیقی جائزہ: THE LEGAL STATUS OF CONTEMPORARY TAKAFUL IN PAKISTAN AND ITS JURISPRUDENTIAL POSITION: A CRITICAL ASSESSMENT (Zia e Tahqeeq, 2025)
In the eyes of Islamic Shari'ah, safeguarding the dangers of life andproperty is an essential requirement of human life. This is called “hajah” in the term of Islamic jurisprudence. Therefore, the establishment of an alternative system of traditional insurance is a Shariah requirement in the opinion of many Islamic scholars. Alternatively, modern titles are discussed under two titles; Islamic Insurance and Takful, although the second title is more preferable. Takaful is not in any way disrespectful to Islamic value of Tawakkul, because leaving of means is not required by Shari'ahat all, but reality is to trust Allah for the desired results by adopting the means available. The Takful is an alternative system to the traditional insurance system, which has been established on the basis of Islamic principles ofcooperation, devotion and mutual sympathy. Modern Islamic scholars have sought help from the three jurisprudential terminologies for adaptation the system of Takful i.e. Hibat al-Thawab, Iltizam al-Tabarru' and Waqf. In the Gulf countries, the agreement of takful has been laid down with concept of Hiba and in Malaysia, with Tabarru' while in Pakistan, India and South Africa the Waqf has been regulated for this purpose. In this article the mode of Waqf of Takaful has been highlighted. Mufti Uthmani described four principles specially to consider in the Waqf model of Takafal, regarding endowment of cash, endower's availing benefits from his endowment, ownership of donation given to the waqf and endless aim of the endowment. Under these principles the Takaful company builds a separate pole of Waqf, it can receive its wages and can also earn its share by acting as a Mudharib of the Waqf pool's wealth and the Waqf pole would be alegal person.